Clinical characteristics and genetic analysis of pediatric patients with sodium channel gene mutation-related childhood epilepsy: a review of 94 patients - Fang, Hongjun; Hu, Wenjing; Kang, Qingyun; Kuang, Xiaojun; Wang, Lijuan; Zhang, Xiao; Liao, Hongmei; Yang, Liming; Yang, Haiyan; Jiang, Zhi; Wu, Liwen (Frontiers in Neurology, 2023)
Objective This study aimed to examine the clinical and gene-mutation characteristics of pediatric patients with sodium channel gene mutation-related childhood epilepsy and to provide a basis for precision treatment and genetic counseling. Methods The clinical data from 94 patients with sodium channel gene mutation-related childhood epilepsy who were treated at Hunan Children's Hospital from August 2012 to December 2022 were retrospectively evaluated, and the clinical characteristics, gene variants, treatment, and follow-up status were analyzed and summarized. Results Our 94 pediatric patients with sodium channel gene variant-related childhood epilepsy comprised 37 girls and 57 boys. The age of disease onset ranged from 1 day to 3 years. We observed seven different sodium channel gene variants, and 55, 14, 9, 6, 6, 2, and 2 patients had SCNlA, SCN2A, SCN8A, SCN9A, SCN1B, SCN11A, and SCN3A variants, respectively. We noted that 52 were reported variants and 42 were novel variants. Among all gene types, SCN1A, SCN2A, and SCN8A variants were associated with an earlier disease onset age. With the exception of the SCN1B, the other six genes were associated with clustering seizures. Except for variants SCN3A and SCN11A, some patients with other variants had status epilepticus (SE). The main diagnosis of children with SCN1A variants was Dravet syndrome (DS) (72.7%), whereas patients with SCN2A and SCN8A variants were mainly diagnosed with various types of epileptic encephalopathy, accounting for 85.7% (12 of 14) and 88.9% (8 of 9) respectively. A total of five cases of sudden unexpected death in epilepsy (SUDEP) occurred in patients with SCN1A, SCN2A, and SCN8A variants. The proportion of benign epilepsy in patients with SCN9A, SCN11A, and SCN1B variants was relatively high, and the epilepsy control rate was higher than the rate of other variant types. Conclusion Sodium channel gene variants involve different epileptic syndromes, and the treatment responses also vary. We herein reported 42 novel variants, and we are also the first ever to report two patients with SCN11A variants, thereby increasing the gene spectrum and phenotypic profile of sodium channel dysfunction. We provide a basis for precision treatment and prognostic assessment.